Comparing electronic monitoring regimes: Length, breadth, depth and weight equals tightness. (January 2021) - Hucklesby, Anthea; Beyens, Kristel; Boone, Miranda
This paper compares the use of electronic monitoring in three European jurisdictions – Belgium, England and Wales and the Netherlands. It suggests that rates of use, the accepted method of comparison in relation to imprisonment and a proxy measure of 'punitiveness' provide a misleading picture when applied to electronic monitoring. This paper transforms Crewe's concept of 'tightness' from a dimension of weight to encompass the overlapping elements of length, breadth, depth and weight to provide a framework for analysing how electronic monitoring regimes are designed to disrupt the lives of monitored individuals. Electronic monitoring regimes are diverse and 'tightness' varied as much, if not more, within as between jurisdictions. Comparisons of 'tightness' also inverted the scale of 'punitiveness' produced using rates of use.